Peptide Functionalization of Gold Nanoparticles for the Detection of Carcinoembryonic Antigen in Blood Plasma via SPR-Based Biosensor - Ermini, Maria Laura; Chadtová Song, Xue; Špringer, Tomáš; Homola, Jiří (Frontiers in Chemistry, 2019)
Nanoparticles functionalized with specific biological recognition molecules play a major role for signal enhancement in surface plasmon resonance (SPR) based biosensors. The functionalization procedure of such nanoparticles is crucial, since it influences their interactions with the environment and determines their applicability to biomolecular detection in complex matrices. In this work we show how the ζ-potential (Zpot) of bio-functionalized gold spherical NPs (Bio-NPs) is related to the SPR sensor response enhancement of an immune-sandwich-assay for the detection of the carcinoembryonic antigen (CEA), a cancer marker for colorectal carcinomas. In particular, we prepare bio-functional nanoparticles by varying the amount of ligand bound on their surface. Specific and non-specific sensor responses, reproducibility, and colloidal stability of those bio-functional nanoparticles are measured via SPR and compared to ζ-potential values. Those parameters are first measured in buffer solution, then when the surface of the biosensor is exposed to 100% blood plasma, and finally when the nanoparticles are immersed in blood plasma and flowed overnight on the biosensor. We found that ζ-potential values can guide the design of bio-functional NPs with improved binding efficiency and reduced non-specific sensor response, suitable reproducibility and colloidal stability, even in complex matrixes like blood plasma.